О наилучших приближениях и колмогоровских поперечниках классов Бесова периодических функций многих переменных - Романюк, А.С. (Український математичний журнал, 1995)
Order estimates are obtained for the best approximations of the classesB 1, θ r in the spaceL q with 1<q<∞ and classesB ∞, θ r in a uniform metric. The behavior of Kolmogorov widths of the classesB p, θ r ,1<p≤∞, in the metric of L∞ is studied.